INDEKS KUNING TELUR DAN NILAI HAUGH UNIT TELUR PUYUH (Coturnix coturnix japonica L.) SETELAH PEMBERIAN TEPUNG KUNYIT (Curcuma longa L.) - Dian Tri Kusumastuti; Koen Praseno; Tyas Rini Saraswati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2012)
This aim of this research was to analyze the effect of supplemented Curcuma longa L. powder to yolk index and haugh unit. A total number of 60 DOQ were distributed into 4 treatments. Each treatment use 3 quails and repeated 5 times. The control diet did not contains Curcuma longa L. powder (P0), the other diets were supplemented with 13,5 mg/quail/day (P1); 27 mg/quail/day (P2); 54 mg/quail/day (P2). The trial lasted for 60 days. The data were analyzed with anova (analysis of variants). Supplemented Curcuma longa L. powder had no effect on any parameters. The diets have not changes yolk index and haugh unit.Key words : Turmeric powder, quail (Coturnix coturnix japonica L.), yolk index, haugh unit.